O ensino e aprendizagem de expressões numéricas para 5ª série do ensino fundamental com a utilização do jogo Contig 60® - Silva, Graziele Cristine Moraes da (2009)
This research aims to investigate the ownership of the numerical expression for students in 5th grade of elementary school, from conversions of Semiotics Representation Registers which will be addressed in this paper the following records: material, natural language and numerical, with the completion of arithmetic processing, and using as a tool the game Contig 60®. We have as a theoretical framework of the Didactic Situations Theory from Guy Brousseau and Semiotics Representation Registers of Raymond Duval. The research was qualitative and as a method it was adopted some assumptions of Engineering Teaching. The teaching sequence was developed to allow students interaction with the activities without requiring the use of rules for the resolution of the problem-situations. To do so, we used the strategy of the game Contig 60®, because it has the characteristic to develop the thinking and stimulate discussion. We stressed the importance of teaching mathematics with the use of games, because playing the student is concerned not with the error, but to participate in the activity, moreover, he can often play the role of researcher in the construction of knowledge. After intervention with the strategy game Contig 60® it was observed that the students improved knowledge on the numerical expression and use as a tool for modeling the problem-situations, and perform the treatments and conversions proposed satisfactorily